Pengaruh Kalsium dalam Makanan Terhadap Penurunan Tekanan Darah - Gracia J. Winaktu (Jurnal Kedokteran Meditek, 2011)
Abstrackblood pressure is determined by cardiac output (cardiac output) and peripheral resistance. The relationship between inputs of calcium (Ca) with decreased blood pressure of essential hypertensive patients’ was first proposed b addison in 1924. Ca is a mineral that is essential for the human body. Calcium helps in activating enzymes that stimulate many essential chemical reaction in the body also plays a role in blood coagulation. Ca can only be absorbed by the intestine about 35%, due to relatively low degree of solubility. Approximately 90% of the input Ca in the diet excreted in the feces each day. Parathyroid hormone is released to maintain the concentration of Ca ions, will increase the influx of extracellular to intracelluler Ca ions, so that the intracellular Ca ion concentration is very high. The inputs of Ca hypertensive patients are lower than normal people. This means that the lack of input of Ca in the diet will lead to increased blood pressure.Key words : Calcium, hypertensive essential, parathyroid hormone.